The impact of health and environmental messaging with and without product filtering in complex retail markets: the case of pulses - Gustafson, Christopher R.; Gitungwa, Henriette; Sapkota, Sushil C.; Rose, Devin J. (Frontiers in Nutrition, 2024)
Multiple barriers exist to healthy and environmentally sustainable food choices. Limited consumer understanding of the health and environmental implications of food choices complicates their abilities to make choices that lead to desired outcomes. The complexity of the retail environment itself may crowd out less immediate motivations to address health or environment. Even if consumers understand general impacts of food choices on health and environmental outcomes, there may be non-negligible time and search costs to identifying the products that meet consumers' needs. In many food categories, the foods containing attributes that help achieve health and sustainability outcomes may represent a small percentage of available products. In this research, we examine the case of pulses-beans, chickpeas, lentils, and dry peas. Pulses are nutritious and have a low environmental impact. However, consumption of pulses in the US is quite low, which may be attributable to low consumer knowledge of pulse benefits, as well as difficulty of identifying pulse products in retail environments. Using the USDA-ARS Food Data Central Branded Foods database, pulse-based foods represented only 4% of products across food categories in which pulses are present as ingredients. In this research, we examine the choice of pulse-based foods in three conditions: 1) a control condition, 2) a messaging condition communicating the health and environmental benefits of pulse products, and 3) a paired messaging condition with a choice environment intervention that allows respondents to choose to filter products to those that contain pulses. We find slight, but significant, increases in pulse choice in the messaging only condition relative to the control condition, but dramatic and highly significant increases when participants can filter the products to easily view pulse products. We also find evidence for knowledge being a barrier to healthy/sustainable food choice. Participants exposed to the messaging were more likely to view pulses as environmentally beneficial, and less likely to report that they did not know the health or environmental impacts of pulse foods. In conclusion, we find that paired messaging and filtering interventions significantly increase the choice of pulse-based foods, which offer both human health and sustainability benefits.